3D printed testing aids for radiographic quality control. Issue 5 (6th April 2019) - Ogden, Kent M.; Morabito, Kristin E.; Depew, Paul K.
Abstract: Quality control testing of radiographic and fluoroscopic imaging systems requires positioning of test objects in the x‐ray beam in a precise and repeatable fashion. In this work we present several three‐dimensional (3D) printed testing aids that improve efficiency, accuracy, and repeatability of quality control testing. We also present a new device for determining the location of the perpendicular ray in radiographic systems. These devices were designed in an open source software program (OpenScad, http://www.openscad.org ) and 3D models were saved in .stl format for printing. The models were printed on either a MakerBot Replicator 2 or Replicator Z18 printer (MakerBot Industries, LLC, Brooklyn, NY). The testing aids were printed using polylactic acid (PLA) filament. To investigate the radiographic characteristics of the PLA used, test articles were printed and used to measure the half‐value layer (HVL) thicknesses in mm of PLA and half‐value densities (HVD) in g/cm 2 of PLA for two different colors and over a wide range of radiographic beam qualities, using a portable fluoroscopic c‐arm system. HVL thicknesses of clear PLA ranged from approximately 20 mm at 50 kV nominal tube voltage to 27 mm at 120 kV nominal tube voltage. For green PLA, the HVL thickness was 19 mm at 50 kV tube voltage and 25.7 mm at 120 kV tube voltage. The HVD of clear PLA ranged from 2.37 g/cm 2 at 50 kV nominal tube voltage to 3.19 g/cm 2 at 120 kV nominal tube voltage. For green PLA, the HVD was 2.35 g/cm 2 at 50 kV tube voltage and 3.17 g/cm 2 at 120 kV tube voltage. The cost of the devices range from under 2 to approximately 20 in materials. The files used to create the models are freely available athttps://github.com/Upstate3DLab/3D-Printed-Radiographic-Test-Tools .